Parents’ expectations regarding case management for rare diseases in Switzerland: mixed-method findings from an online survey (Swiss Medical Weekly, 2024)
AIMS OF THE STUDY: This pilot study aims to enhance understanding by examining parents’ specific views on the requirements, content and objectives of case management and advanced care coordination for children with rare diseases during childhood. The findings of this study are expected to offer valuable insights and recommendations for existing and future initiatives in clinical practice and research, with the goal of improving the comprehensive, child-centred and family-orientated approach to case management.METHODS: This pilot study is part of an ongoing prospective study (SPACE), involving parents and families from various networks in Switzerland. Participants were parents recruited from the Children with Rare Diseases (KMSK) network consisting of families with children with rare diseases. The survey questionnaire covered demographic information; expectations and perceived need for case management; assessment of their quality of life and their child’s suffering; and evaluation of interprofessional and interdisciplinary communication. Qualitative data from free-response answers were analysed using Mayring’s content analysis and descriptive statistics were used to analyse quantitative data from Likert-scale questions.RESULTS: The study included 108 respondent families from among the 775 in the KMSK, a 14% response rate. The age of their children ranged from 0.4 to 24 years (mean: 8) and their level of suffering in the past six months varied, with 31.5% indicating intense or very intense suffering. In terms of case management, 15.8% of families reported access while 32.4% expressed a need but did not have access to it. The study identified three categories of parental expectations regarding case management, emphasising the importance of interprofessional collaboration, effective communication and comprehensive support.CONCLUSIONS: The findings shed light on the high need for case management support with a current undersupply in Switzerland and an association with reduced parental quality of life, highlighting the necessity for diverse support and assistance to effectively manage the challenges faced by families with children with rare diseases.